2014
DOI: 10.1002/lary.24827
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phonation time and magnitude dose on vocal fold epithelial genes, barrier integrity, and function

Abstract: Objective To investigate the effects of increasing time and magnitude doses of vibration exposure on transcription of the vocal fold's junctional proteins, structural alterations, and functional tissue outcomes. Study Design Animal study. Methods 100 New Zealand White breeder rabbits were studied. Dependent variables were measured in response to increasing time doses (30, 60, or 120 minutes) and magnitude doses (control, modal intensity, and raised intensity) of vibration exposure. Messenger RNA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 31 publications
(54 reference statements)
2
39
0
Order By: Relevance
“…The maximum time-dose of 120 minutes was based on work by Solomon, Glaze, Arnold, and van Mersbergen (24) that revealed decreased vocal function after 120 minutes of loud speaking in humans. Subsequent work in our laboratory confirmed that 30- and 60-minute time-doses led to observations of structural and functional vocal fold tissue changes (20, 21). Modal intensity phonation was elicited with mean electrical stimulation of 1.56 mA ( SD = 0.63) and constant airflow rate of 85.03 mL/s ( SD = 0.00).…”
Section: Methodsmentioning
confidence: 61%
“…The maximum time-dose of 120 minutes was based on work by Solomon, Glaze, Arnold, and van Mersbergen (24) that revealed decreased vocal function after 120 minutes of loud speaking in humans. Subsequent work in our laboratory confirmed that 30- and 60-minute time-doses led to observations of structural and functional vocal fold tissue changes (20, 21). Modal intensity phonation was elicited with mean electrical stimulation of 1.56 mA ( SD = 0.63) and constant airflow rate of 85.03 mL/s ( SD = 0.00).…”
Section: Methodsmentioning
confidence: 61%
“…The current study simulated a condition of vibration that best represents the physiologic function of vocal fold vibration. This vibratory condition was selected based on previously reported morphological features of intact paracellular spaces and basement membrane, and a lack of functional tissue changes as measured by transepithelial resistance [Kojima et al, 2014a]. In contrast, raised intensity phonation was not studied due to evidence of pathologic damage, primarily epithelial tissue obligation, which could lead to less viable tissue for analysis [Kojima et al, 2014a].…”
Section: Discussionmentioning
confidence: 99%
“…This vibratory condition was selected based on previously reported morphological features of intact paracellular spaces and basement membrane, and a lack of functional tissue changes as measured by transepithelial resistance [Kojima et al, 2014a]. In contrast, raised intensity phonation was not studied due to evidence of pathologic damage, primarily epithelial tissue obligation, which could lead to less viable tissue for analysis [Kojima et al, 2014a]. During normal cycles of vibration, we hypothesize that biomechanically-induced stresses signal vocal fold epithelial cells to undergo apoptosis to regularly renew the tissue and maintain homeostasis, as has been reported in the intestinal epithelium [Marchiando et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations